Aerosol generating product
Patent Information
- Application Number
- CN202380024224.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-12
- Publication Date
- 2025-02-18
AI Technical Summary
In existing heated tobacco technology, it is difficult to achieve a balance between the magnetic properties, Curie temperature, and permeability of the sensor material, resulting in uneven heating and the risk of releasing harmful substances and combustion.
By using a single-layer uniform soft magnetic alloy material, and by controlling the grain size and composition ratio, a sensor component suitable for resonant wireless power transmission is prepared by ensuring rapid heating during the preheating stage and demagnetization before 400℃. Combined with specific process flows such as melting, remelting, hot forging, cold rolling and annealing.
It has enabled stable heating of aerosol-generated products in the field of heated non-combustible tobacco, reducing the release of harmful substances and the risk of combustion, and improving the user experience.
Smart Images

Figure CN119486612A_ABST
Abstract
Description
An aerosol generating product Technical Field
[0001] The present invention relates to the technical field of heat-not-burn tobacco, and in particular to an aerosol-generating product. Background Art
[0002] In the field of heat-not-burn tobacco (Heat Not Burn), the aerosol generating system includes an aerosol generating device and an aerosol generating product. The Magnetic Coupling Resonance Wireless Power Transfer (MCR-WPT) system has the characteristics of high energy conversion efficiency and non-contact heating, which can efficiently heat tobacco products and improve the robustness of the heating system. Developing an aerosol generating device based on the principle of resonant wireless power transmission is a preferred solution. Among them, the sensor is set in the aerosol generating device or the receptor is set in the aerosol generating product, and the receptor heats the aerosol generating product based on the principle of resonant wireless power transmission.
[0003] The sensor material must possess appropriate high-frequency magnetic permeability, resistivity, and dimensions to match the specific coil parameters and external circuit characteristics. This ensures it maintains a resonant state during the basic constant temperature phase, achieving the goal of heating cigarettes without burning them. The heating process of the aerosol-generating product using the sensor includes a preheating phase and a basic constant temperature phase. To ensure a satisfying user experience, rapid temperature increases are often required during the preheating phase to achieve efficient release of volatile smoke substances. Due to the automatic temperature control characteristics of the soft magnetic core material, during the preheating process, the core material's temperature can continue to rise to the Curie point. Subsequently, the core material demagnetizes and cools down because it can no longer absorb energy from the external magnetic field. During the puffing process, the core material's temperature drops significantly due to the influx of cold air, and the material's magnetic properties recover, thus forming a heating-and-cooling cycle and achieving the goal of automatic temperature control.
[0004] However, temperatures exceeding 400°C increase the risk of harmful emissions and tobacco combustion. To prevent the release of harmful components and mitigate potential combustion risks, the susceptor material's magnetothermal conversion capacity and Curie temperature must be reduced during electromagnetic induction. This, however, falls short of the operating temperature requirements for heat-not-burn cigarettes. Therefore, it is necessary to provide a susceptor material that strikes a balance between application size, magnetic permeability, saturation magnetic induction intensity, coercivity, resistivity, and Curie temperature to meet magnetothermal conversion requirements for heat-not-burn applications, mitigating the problem of insufficient or excessive heating of the aerosol-generating substrate by the heater.
[0005] Summary of the Invention
[0006] In view of this, the present application provides an aerosol generating product that meets the requirements of the aerosol generating device sensor for magnetic properties and Curie temperature, ensures rapid temperature rise during the preheating stage, and undergoes ferromagnetic to paramagnetic transition and complete demagnetization before 400°C, thereby alleviating the heater's excessive heating of the aerosol generating substrate.
[0007] In order to achieve the above technical objectives, this application adopts the following technical solutions:
[0008] In a first aspect, the present application provides an aerosol-generating product for generating an inhalable aerosol when heated, comprising an aerosol-generating matrix segment, the aerosol-generating matrix segment comprising an aerosol-generating matrix and a receptor assembly, the receptor assembly inductively heating the aerosol-forming matrix under the influence of an alternating magnetic field, the material of the receptor assembly being a soft magnetic alloy, the soft magnetic alloy being a single-layer structure with uniform element distribution; the average particle size of the soft magnetic alloy grains being 50 to 70 μm, and the grain size grade being 5.5 to 4.5.
[0009] Preferably, the components of the soft magnetic alloy include iron, molybdenum and nickel, the mass of molybdenum accounts for 3.5% to 6% of the total mass of the soft magnetic alloy, and the mass of nickel accounts for 77% to 81% of the total mass of the soft magnetic alloy.
[0010] Preferably, the soft magnetic alloy further comprises chromium, and the mass of chromium accounts for 0.2-0.5% of the total mass of the soft magnetic alloy.
[0011] Preferably, the soft magnetic alloy further comprises manganese, and the mass of manganese accounts for 0.1 to 0.5% of the total mass of the soft magnetic alloy.
[0012] Preferably, the soft magnetic alloy further comprises silicon and aluminum, the silicon content is 0.1% to 0.4%, and the mass of aluminum accounts for 0.15 to 0.7% of the total mass of the soft magnetic alloy.
[0013] Preferably, the soft magnetic alloy comprises the following components in mass fractions: 77-81 parts nickel, 3.5-6.0 parts molybdenum, 0.2-0.5 parts chromium, 0.1-0.5 parts manganese, 0.1-0.4 parts silicon, 0.15-0.7 parts aluminum, and the balance approximately 11-18 parts iron.
[0014] Preferably, the aerosol-generating substrate segment has an applied thickness of 0.03 to 0.18 mm, a width of 1.5 to 4.5 mm and a length of 9 to 18 mm.
[0015] Preferably, the aerosol-generating product for generating an inhalable aerosol when heated further comprises a filter segment and a cooling segment, wherein the cooling segment is located between the aerosol-generating substrate segment and the filter segment; the aerosol-generating substrate is made of tobacco material or non-tobacco material and is distributed in a filamentous, sheet-like or granular form, and the receptor assembly is wrapped by the aerosol-generating substrate.
[0016] The preparation method of the sensor assembly comprises the following steps:
[0017] S1 weighed by mass alloy raw materials and coke, followed by smelting, remelting, hot forging blanking, hot rolling, cold rolling process to obtain cold-rolled material;
[0018] S2. Place the cold-rolled material and the mixed material in a vacuum hydrogen annealing furnace for annealing at a temperature of 1000-1200°C, a holding time of 70-120 minutes, a cooling rate of 150-220°C / h, and after the temperature drops to 580-630°C, air cool or furnace cool to 100-200°C.
[0019] Preferably, the mixed powder is a 100-300 mesh mixed powder, including a mixture of Fe2O3, MnO, SiO2, Al2O3, MgO, and C powders; the volume ratio of the mixed powder to the cold-rolled material is 0.05-0.15:100.
[0020] The beneficial effects of this application are as follows:
[0021] The present invention provides an aerosol generating product for generating an inhalable aerosol when heated, comprising an aerosol generating substrate segment, the aerosol generating substrate segment comprising an aerosol generating substrate and a sensor component, the sensor component inductively heating the homogeneous tobacco material of the aerosol generating substrate segment under the influence of an alternating magnetic field to form an aerosol for a user to inhale, the sensor component is a soft magnetic alloy having only a single-layer homogeneous structure, which realizes the application in the field of heating tobacco without burning, the soft magnetic alloy can realize non-contact heating of the aerosol generating substrate based on the principle of resonant wireless power transmission, the soft magnetic alloy with a single-layer homogeneous structure has a stable Curie temperature range, and is passed through the By controlling the average grain size of the soft magnetic alloy to be between 50 and 70 μm and the grain size level to be between 5.5 and 4.5, the saturation magnetic induction intensity is greatly affected. For the magnetization mode mainly characterized by magnetic domain rotation, the larger the grain size of the sensor component, the greater the saturation magnetic induction intensity. The appropriate magnetic permeability, low coercive force, and appropriate resistivity at high frequencies ensure rapid temperature rise in the preheating stage and enable the sensor component to be completely demagnetized before 400°C, thereby stopping the heating of the aerosol generating matrix. While satisfying the user experience, it minimizes the risk of users using aerosol products and alleviates the behavior of the heater overheating the aerosol generating matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a 100X metallographic microscope identification image of a soft magnetic alloy component;
[0023] FIG2 is a 200X metallographic microscope identification image of a soft magnetic alloy component;
[0024] FIG3 is a field emission scanning electron microscope identification image of a typical area of a soft magnetic alloy component;
[0025] FIG4 is an elemental analysis energy spectrum diagram of a characteristic point at a defect in area A of FIG3 ;
[0026] FIG5 is an elemental analysis energy spectrum diagram of a characteristic point at a defect in area B of FIG3 ;
[0027] FIG6 is an elemental analysis energy spectrum diagram of a characteristic point at a defect in area C of FIG3 ;
[0028] FIG7 is a field emission scanning electron microscope identification image of a typical area of a soft magnetic alloy component;
[0029] FIG8 is a hysteresis B-H curve diagram of a soft magnetic alloy component;
[0030] FIG9 is a hysteresis B-H curve diagram of a soft magnetic alloy component;
[0031] FIG10 is a schematic diagram of the grayscale cross section of a soft magnetic alloy;
[0032] FIG11 is a schematic diagram of the magnetization intensity-temperature curve and its derivative curve of the soft magnetic alloy;
[0033] FIG12 is a schematic diagram of the magnetization intensity-temperature curve and its derivative curve of the soft magnetic alloy;
[0034] Figure 13 shows a ternary structure aerosol generating product;
[0035] FIG14 is a quaternary structure aerosol generating product;
[0036] FIG15 is a schematic diagram of a time-temperature curve of a soft magnetic alloy in an aerosol generating device;
[0037] In the figure: 1. Aerosol generation matrix section; 2. Cooling section; 3. Mouth section; 4. Anti-leakage section. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0039] In the field of heat-not-burn tobacco products, aerosol generating devices have the characteristic of being able to automatically control the temperature according to the soft magnetic core material. During the preheating process, the sensor material continues to heat up to the Curie point, and then the sensor material loses magnetism. During the inhalation process, air enters the cigarette core section and contacts the sensor material, causing the temperature of the sensor material to drop, restoring the magnetic permeability, thereby forming a heating-cooling cycle and achieving the purpose of automatic temperature control. However, in the field of heat-not-burn tobacco products, existing alloy technologies are unable to meet the design requirements of magnetic properties, Curie temperature and magnetic permeability, and the prepared alloy materials are all multi-layer materials. Since the Curie temperature points of two or more layers of sensor materials are different, there is a risk that the heating temperature of the aerosol generating product will exceed 400°C, significantly increasing the release of harmful components and the risk of combustion. Therefore, the present invention provides a homogeneous cigarette core material with only a single-layer structure, which realizes non-contact heating of aerosol generating products based on the principle of resonant wireless power transmission. The temperature rises rapidly during the preheating stage, and heating is stopped after the ferromagnet-paramagnet transformation occurs before 400°C and the magnetism is completely lost. This helps to improve the user experience while effectively reducing the release of harmful substances and combustion risks of aerosol products.
[0040] The present application provides an aerosol-generating product for generating an inhalable aerosol when heated, comprising an aerosol-generating matrix segment, wherein the matrix segment comprises an aerosol-generating matrix and a receptor assembly. The receptor assembly induction heats the aerosol-forming matrix under the influence of an alternating magnetic field. The material of the receptor assembly is a soft magnetic alloy having a uniform single-layer structure. The average particle size of the soft magnetic alloy grains is 50 to 70 μm, and the grain size grade is 5.5 to 4.5.
[0041] Soft magnetic alloys meet both the magnetic properties and Curie temperature requirements of aerosol generating device receptors, ensuring rapid temperature rise during the preheating phase and undergoing a ferromagnetic-to-paramagnetic transition and complete demagnetization before 400°C. This enables their application in electromagnetic induction heating of tobacco products with automatic temperature control based on contactless radio transmission principles, significantly reducing the risk of harmful substances and combustion from heated homogenized tobacco materials. The grain size of soft magnetic alloys affects the saturation magnetic induction intensity of the receptors. For magnetization primarily driven by magnetic domain rotation, larger grain sizes result in greater saturation magnetic induction intensity.
[0042] The single-layer structure defined in the present invention satisfies the following two conditions: the manufacturing process of the soft magnetic alloy only includes smelting, remelting, hot forging, hot rolling, cold rolling, and annealing processes, and does not include any of the following processes: electroplating, coating, welding, and cladding; in the grayscale image of the soft magnetic alloy taken under a scanning electron microscope, the overall image contrast is basically uniform in the range of 100 to 3000 times and can be identified by the naked eye, and the color area with the widest area in the main part of the soft magnetic alloy accounts for at least 95% of the area value of the entire area of the soft magnetic alloy.
[0043] The components of the soft magnetic alloy include molybdenum and nickel. The mass of molybdenum accounts for 3.5% to 6% of the total mass of the soft magnetic alloy, the mass of nickel accounts for 77% to 81% of the total mass of the soft magnetic alloy, and the balance is iron. The mass ratio of nickel to molybdenum is 15.2 to 16.5:1.
[0044] The soft magnetic alloy of the present application includes, in addition to iron, nickel, and molybdenum, one or more of Al, Cr, Mn, and Cu, and other metals or non-metals that can be used for alloying. The elements that can be included are, but are not limited to, Si, C, O, S, and P. In some embodiments, the surface of the soft magnetic alloy of the present embodiment is locally treated to form defects.
[0045] The Curie temperature of a soft magnetic alloy is primarily related to the spatial arrangement of magnetic and non-magnetic atoms. The soft magnetic alloy in this design controls the nickel and molybdenum composition ratio, adding a certain proportion of molybdenum to reduce the relative nickel content. This helps increase the alloy's initial magnetic permeability and resistivity. Furthermore, molybdenum is a paramagnetic element, forming a solid solution with the ferromagnetic elements Ni and Fe. This solid solution behavior causes the outer electrons of the molybdenum atoms to transfer to the ferromagnetic atoms, causing spin reversal and weakening the magnetic exchange interaction of the ferromagnetic atoms. This solid solution behavior also increases the lattice structure of the ferromagnetic material, increasing the distance between the ferromagnetic elements and weakening the magnetic exchange interaction of the ferromagnetic atoms. This reduces the material's remanence and coercivity, while increasing the initial magnetic permeability. Molybdenum is added in two ways: during the initial batching process or in the later stages of refining. A suitable nickel-molybdenum ratio helps control the Curie temperature of the soft magnetic alloy, maintaining it between 350 and 400°C.
[0046] The soft magnetic alloy also includes chromium, which accounts for 0.2 to 0.5% of the total mass of the soft magnetic alloy. The addition of chromium reduces the relative content of nickel, which is beneficial to improving the initial magnetic permeability, enhancing the alloy's oxidation resistance, and effectively reducing coercive force.
[0047] The components of the soft magnetic alloy also include manganese, which accounts for 0.1 to 0.5% of the total mass of the soft magnetic alloy. It can be added during the refining process to achieve the purpose of alloying. At the same time, the Mn element is easily combined with the S element, avoiding the formation of FeS by Fe and S elements, which increases the hot brittleness of the alloy.
[0048] The soft magnetic alloy also includes silicon and aluminum, with the silicon content ranging from 0.1% to 0.4% and the aluminum content ranging from 0.15% to 0.7%. Preferably, the mass ratio of manganese to silicon is 0.9 to 2.95:1. Manganese, silicon, and aluminum effectively reduce the high proportion of oxides within the alloy, effectively reducing its coercivity and offsetting the increase in the coercivity of the soft magnetic alloy caused by the introduction of some oxides during the annealing process.
[0049] Furthermore, the addition of a small amount of Al tends to cause lattice distortion in the arrangement of metal atoms, enhancing the solid solution behavior of Mo in the ferromagnetic Ni and Fe elements. This enhanced solid solution behavior increases the lattice structure of the ferromagnetic material and the distance between ferromagnetic elements, which in turn weakens the magnetic exchange interaction between ferromagnetic atoms, reducing the material's remanence and coercivity while increasing the initial magnetic permeability. This increase in initial magnetic permeability is beneficial for maintaining good magnetic properties after the introduction of surface oxidation in the later stages of annealing.
[0050] The mass ratio of nickel to iron in the components of the soft magnetic alloy is 4.5 to 5:1, which is conducive to forming an optimal short-range ordered structure near Ni3Fe, at which time it has the smallest magnetocrystalline anisotropy constant and saturation magnetostriction coefficient.
[0051] The soft magnetic alloy comprises the following components by mass: 77 to 81 parts of nickel, 3.5 to 6.0 parts of molybdenum, 0.2 to 0.5 parts of chromium, 0.1 to 0.5 parts of manganese, 0.1 to 0.4 parts of silicon, 0.15 to 0.7 parts of aluminum, and the balance being approximately 11 to 18 parts of iron.
[0052] The thickness of the susceptor assembly is 0.03-0.18 mm, the width is 1.5-4.5 mm, and the length is 9-18 mm. Preferably, the thickness is 0.105-0.15 mm, and the width is 2-4 mm. Preferably, the length of the material is 10-14 mm.
[0053] The Curie temperature of the soft magnetic alloy is 350-400°C. Preferably, the Curie temperature of the soft magnetic alloy is 380-395°C. Near the Curie temperature, the magnetic permeability of the soft magnetic alloy component of the present application will drop significantly to close to 0, and the power loss of the soft magnetic alloy component will be significantly reduced and close to 0. A Curie temperature not higher than 400°C can avoid the release of harmful components and the potential risk of combustion.
[0054] When the thickness of the soft magnetic alloy is 0.1 to 0.18 mm and the magnetic field frequency is 60 Hz, the saturation magnetic induction intensity between 0.4 and 20 Oe is 7000 to 10000 Gs. Preferably, the saturation magnetic induction intensity is 7000 to 9000 Gs. More preferably, the saturation magnetic induction intensity is 7000 to 8500 Gs. The saturation magnetic induction intensity of this scheme is used to meet the rapid heating process of the aerosol generation matrix section preheating stage, significantly improving the magnetic flux value in the coil.
[0055] According to the ASTM A772 / A772M magnetic permeability test standard, the maximum magnetic permeability of the soft magnetic alloy is 120 to 275 mH / m when the thickness is 0.1 to 0.18 mm and the magnetic field frequency is 60 Hz. Preferably, the maximum magnetic permeability is 150 to 220 mH / m, and more preferably, the maximum magnetic permeability is 190 to 200 mH / m. Within the maximum magnetic permeability range of this scheme, a certain skin depth can be guaranteed, thereby ensuring that a certain amount of eddy current loss is effectively converted into heat energy and absorbed by the aerosol generating matrix to produce aerosol.
[0056] The soft magnetic alloy has a coercive force of 0.1 to 4 A / m when the thickness is 0.1 to 0.18 mm and the magnetic field frequency is 60 Hz. More preferably, the coercive force is 0.1 to 2 A / m, and more preferably, the coercive force is 0.1 to 1.5 A / m. Within this range, the magnetic properties of the soft magnetic alloy component are highly stable.
[0057] The soft magnetic alloy has a room temperature resistivity of 40 to 100 μΩcm when the thickness is 0.1 to 0.18 mm and the magnetic field frequency is 60 Hz. Preferably, the room temperature resistivity is 40 to 80 μΩcm, and more preferably, the room temperature resistivity is 40 to 70 μΩcm.
[0058] As shown in Figures 14 and 15, the present application provides an aerosol-generating product, which also has a filter segment 3 and a cooling segment 2. The cooling segment 2 is located between the aerosol-generating matrix segment 1 and the filter segment 3. The aerosol-generating matrix is made of tobacco material or non-tobacco material and is distributed in a filamentous, sheet-like or granular form. The receptor assembly is wrapped by the aerosol-generating matrix. Specifically, the sheet-like or filamentous tobacco or non-tobacco material surrounds and wraps the receptor assembly, and the granular tobacco or non-tobacco material buries the receptor assembly in a stacked manner. Figure 14 is a ternary structure aerosol-generating product, including a filter segment 3, a cooling segment 2, and an aerosol-generating matrix segment 1; Figure 15 is a quaternary structure aerosol-generating product, including a filter segment 3, a cooling segment 2, an aerosol-generating matrix segment 1 and an anti-leakage segment 4; the aerosol-generating matrix segment 1 includes an aerosol-generating matrix and the above-mentioned soft magnetic alloy component. The soft magnetic alloy heats the aerosol-generating matrix based on the principle of electromagnetic induction heating. The aerosol-generating matrix can be tobacco flakes, cut tobacco, cut stems, expanded cut tobacco, expanded cut stems, or tobacco granules. It typically contains smoking substances such as glycerin and propylene glycol, nicotine, and cannabinoids. Flavoring substances such as flavorings and fragrances may also be added. After heating, the aerosol-generating matrix releases volatile smoking substances, nicotine, cannabinoids, and flavoring substances to form vapor. This vapor is then cooled during inhalation. Due to a nucleation mechanism, the vapor condenses into droplets. When the temperature is sufficiently low and the number of droplets is sufficient, they coalesce to form large-sized aerosol droplets. The cooling section 2 lowers the flue gas temperature to further support the cooling of volatile substances from the aerosol-generating matrix to form an aerosol. It typically has a clear airway to transport the vapor or aerosol. The cooling mechanism can be convective heat transfer or a phase change in the cooling material. A mouthpiece is provided away from the aerosol-generating matrix segment. This mouthpiece contacts the oral cavity to support lung inhalation and simultaneously filters harmful substances. The mouthpiece is often made of a dense fiber bundle, which effectively traps harmful substances in smoke. Furthermore, a leakage prevention section 4 is provided at the other end of the aerosol-generating matrix segment to prevent aerosol or vapor from escaping, thereby avoiding contamination of the aerosol-generating device and maintaining cleanliness.
[0059] The preparation method of the sensor assembly comprises the following steps:
[0060] S1 weighed by mass alloy raw materials and coke, followed by smelting, remelting, hot forging blanking, hot rolling, cold rolling process to obtain cold-rolled material;
[0061] S2. The cold-rolled material and the mixed powder are placed in a vacuum hydrogen annealing furnace for annealing at a temperature of 1000-1200°C, a holding time of 70-120 min, and a cooling rate of 150-220°C / h; the mixed powder includes a mixture of Fe, MnO, SiO2, Al2O3, and C powders.
[0062] The annealing process has a significant effect on the magnetic properties of soft magnetic alloys, including magnetic permeability and saturation magnetic induction intensity. When the annealing temperature is higher and the holding time is longer, the purity of the soft magnetic alloy will increase and the grain size will increase, which will lead to an increase in the maximum magnetic permeability and an increase in the saturation magnetic induction intensity. The above annealing temperature and holding time are conducive to the appropriate adjustment of the maximum magnetic permeability and saturation magnetic induction intensity, and by controlling the cooling rate, especially the cooling rate of the secondary cooling starting at about 600 ° C, and adopting a rapid cooling method of air cooling, the initial magnetic permeability of the alloy can be significantly increased, while only causing a slight increase in the maximum relative magnetic permeability, ultimately achieving a slightly higher saturation magnetic induction intensity and an appropriate maximum magnetic permeability.
[0063] The mixed powder oxidizes the alloy surface. This oxidation process significantly reduces the material's maximum magnetic permeability, increases its coercivity, and decreases its resistivity. To achieve the goal of producing a material with reduced maximum magnetic permeability, the present invention utilizes a controlled method for adding and preparing the mixed powder, resulting in a stable production process and effective control of inclusions on the alloy surface.
[0064] After mixing 30-50 parts of Fe powder, 25-30 parts of SiO2, 10-15 parts of C powder, 15-19 parts of Al2O3 and 1-5 parts of MnO, inclusion elements including but not limited to Al, Si, C, O, Mn, S and P may be introduced into the alloy. These inclusion elements mainly exist in the form of metal oxides or sulfides. These non-metallic inclusions will cause the alloy grain size to increase, produce a pinning effect, and cause the magnetic domains to increase and become more complicated, resulting in a decrease in the magnetic permeability of the alloy, a slight increase in the saturation magnetic induction intensity, and an increase in the coercive force.
[0065] On the basis of controlling the grain size and nickel-molybdenum ratio of the soft magnetic alloy, a special surface oxidation treatment method is used in the annealing process to reduce the magnetic permeability of the soft magnetic alloy while maintaining the Curie temperature, saturation magnetic induction intensity, coercive force and resistivity without significant changes, so as to meet the application in the field of heated cigarettes under the automatic temperature control electromagnetic heating process under the principle of non-contact radio transmission.
[0066] The alloy raw materials in step S1 include but are not limited to iron, nickel, molybdenum, chromium, manganese, and silicon. Iron and nickel are added in the smelting step, and nickel or other alloy raw materials are added in the smelting and / or remelting step.
[0067] In some embodiments, the smelting process of step S1 is as follows:
[0068] According to the requirements for the total composition of the soft magnetic alloy product and the purity of the masterbatch, iron, nickel, and molybdenum are weighed. At the same time, coke equivalent to half the total mass of the iron, nickel, and molybdenum is added and placed in the charging area. From the charging area, the vacuum induction melting furnace is added and evacuated. The furnace is then combined for smelting at a smelting temperature of 1500-1600°C and a smelting time of 60-100 minutes. After melting, refining is continued. 0.5 parts of manganese ore with a manganese content of 25% is added during the refining process to achieve the purpose of alloying. The refining time is 0.5-1.5 hours and the refining temperature is 1550-1650°C. After refining, it is poured at 1400-1500°C, then demolded and furnace numbered to obtain an ingot. Other alloys include but are not limited to molybdenum, chromium, manganese, and silicon that meet the requirements for the total composition of the soft magnetic alloy product. In some embodiments, the mass ratio of iron, nickel, and molybdenum in step S1 is 2-3:9-10:0.5-1. Other components can be supplemented or adjusted in the subsequent remelting step.
[0069] In some embodiments, the remelting process of step S1 is as follows:
[0070] The ingot is cut into 5*5*5mm small pieces and polished to remove surface oil and rust. A graphite crucible is lined with a magnesia crucible, and the bottom of the graphite crucible is padded with 0.8-1.5wt% electrolytic nickel plates. The ingot is then placed in the ingot, and 0-0.1wt% fused magnesia is inserted into the gaps in the ingot. The ingot is then placed in a vacuum induction melting furnace and evacuated. The furnace is then combined and smelted at 10kW power at a temperature of 1500-1600°C for 50-80 minutes. 0.06-0.2wt% graphite carbon powder and 0.03-0.07wt% Si-Ca-Ba powder with a particle size of less than 1.0mm are added in three portions at a 2:1 ratio, with an interval of 5-10 minutes between the first and second additions. A third portion is added with 0-0.1wt% molybdenum bars. After the raw materials are added, the refining time is 20 to 40 minutes, the heating power is adjusted to 2 kW, and after the heating is completed, when the temperature drops to 300°C, the circuit is turned off, the vacuum is maintained, and the sample is allowed to cool with the furnace to obtain a remelted ingot.
[0071] After the alloy is first melted and refined in a vacuum induction furnace (i.e., the melting process), its surface is cleaned and a second remelting is performed. This is beneficial for removing elements such as P and S from the alloy, reducing the proportion of non-metallic elements in the alloy to stabilize the alloy composition and subsequent processing stability. During the remelting process, controlled additions of materials or adjustments to the process can effectively control the ratio of non-metallic and metallic elements in the alloy, allowing for secondary adjustments to the alloy composition. At this stage, the alloy composition is sampled and tested to ensure that the alloy composition is within the set range. Subsequently, the soft magnetic alloy is processed through hot forging, hot rolling, and cold rolling to produce materials with a thickness of 0.03 to 0.18 mm. The cold rolled materials are sampled and tested for their magnetic properties, Curie temperature, and resistivity. The details are as follows.
[0072] The types and amounts of raw materials involved in the above-mentioned smelting and remelting steps can be added in batches. In some embodiments, the soft magnetic alloy component includes 77 to 81 parts of nickel, 11 to 18 parts of iron, 3.5 to 6.0 parts of molybdenum, 0.2 to 0.5 parts of chromium, 0.1 to 0.5 parts of manganese, and 0.1 to 0.4 parts of silicon.
[0073] In some embodiments, the hot forging process of step S1 is as follows:
[0074] Depressurize the smelting furnace, take out the crucible and the remelted ingot, place the remelted ingot in a chamber furnace, raise the temperature in the furnace to 1250-1300°C in 50-70 minutes, and after 5-15 minutes, hot forge it into a 20-35 mm flat billet under the action of a 2-ton steam hammer. After surface grinding with a grinding wheel, the billet is obtained.
[0075] In some embodiments, the hot rolling process of step S1 is as follows:
[0076] After the billet is heated to 1150-1250°C, a four-roll reversible hot rolling mill is used and the billet is kept warm for three times with the holding times being 30-60min, 20-40min and 15-30min respectively. The thicknesses after the three hot rolling processes are 15-20mm, 8-15mm and 3-8mm respectively. The deformation temperature range of the hot rolling process is 900-1200°C, and further 1000-1200°C. The surface temperature of the hot-rolled plate is tested with an infrared thermometer. When the temperature is lower than 1000°C, preferably 900°C, the hot rolling is stopped to obtain a hot-rolled material.
[0077] In some embodiments, the cold rolling process of step S1 is as follows:
[0078] The hot rolled material is cold rolled using a four-roll reversible cold rolling mill, and the thickness is initially cold rolled to 1-1.5 mm. The cold rolled material is further rolled to a thickness of 0.03-0.18 mm using a four-roll reversible cold rolling mill to obtain a cold rolled material.
[0079] Before the final annealing process, it is necessary to obtain stable semi-finished and cold-rolled materials with material properties within the expected requirements. The semi-finished materials are then subjected to an annealing process. Annealing helps remove impurities and internal stresses in the alloy, while allowing the alloy to recrystallize, resulting in a disordered and uniform crystal structure.
[0080] In some embodiments, the annealing process of step S2 is:
[0081] Annealing the cold-rolled material involves preparing a 100-300 mesh mixed powder and placing it in a vacuum hydrogen annealing furnace along with the cold-rolled material. The furnace temperature is raised to 1000-1200°C over 60-120 minutes, held for 70-120 minutes, then lowered to 580-630°C at a rate of 150-220°C / hour. The material is then air-cooled or furnace-cooled to 100-200°C before being removed from the furnace. For furnace cooling, the temperature is lowered from 600°C to 300°C over 30-60 minutes at a cooling rate of 300-600°C / hour. For air cooling, the temperature is lowered from 600°C to 300°C over 8-20 minutes at a cooling rate of 900-2250°C / hour. During this annealing process, the alloy surface undergoes a certain degree of oxidation. Appropriate surface oxidation ensures that the material's magnetic properties meet the requirements. The annealing temperature, holding time, cooling rate, and air cooling method selected in this annealing process are conducive to controlling the average grain size between 50 and 70 mm and the grain size between 5.5 and 4.5. The grain size of the material affects the saturation magnetic flux density. For magnetization methods that primarily involve magnetic domain rotation, the larger the alloy grain size, the greater the saturation magnetic flux density.
[0082] During the alloy smelting process, a certain proportion of oxides will be present due to complex factors such as raw material purity, partial metal deoxidation during the smelting process, and contaminants on the furnace wall surface. Common oxides present during the preparation of soft magnetic alloys include MnO, SiO2, and Al2O3. The magnetization of soft magnetic alloys primarily occurs through reversible domain rotation and irreversible domain wall motion. Since magnetic field strengths typically do not exceed 50 Oe in magnetothermal conversion applications such as heat-not-burn tobacco, domain rotation and relatively little domain wall motion predominate in soft magnetic alloys. Increasing the number of oxides, firstly, a demagnetizing field is generated during magnetization, creating magnetic domain structures within the alloy and making magnetization difficult. Secondly, the oxides create a pinning effect within the alloy, increasing hysteresis losses and coercivity, increasing the work required for domain wall motion and making magnetization difficult. The presence of oxides during the preparation process often makes magnetization of soft magnetic alloys difficult, resulting in, for example, a decrease in maximum permeability and an increase in coercivity.
[0083] The soft magnetic alloy of the present application has a large grain size, a high saturation magnetic induction intensity, and a low magnetic permeability, which works together with the molybdenum-nickel component ratio to improve the magnetic properties of the soft magnetic alloy. By adjusting various parameters of the annealing process to control the particle size and particle size level of the soft magnetic alloy, the magnetic permeability of the sensor component is low and the saturation magnetic induction intensity is high. The average grain size is controlled between 50 and 70 μm, and the grain size level is between 5.5 and 4.5, thereby achieving the most preferred properties.
[0084] The mixed powder includes the following components in parts by mass: 30 to 50 parts of Fe powder, 25 to 30 parts of SiO2, 10 to 15 parts of C powder, 15 to 19 parts of Al2O3, and 1 to 5 parts of MnO. Preferably, the particle size of the mixed powder is 100 to 300 meshes.
[0085] Preferably, the volume ratio of the mixed powder to the cold-rolled material is 0.05-0.15:100.
[0086] The soft magnetic alloy obtained by the above process steps has a Curie temperature of 350-400°C when used as an aerosol generation matrix segment for induction heating; the soft magnetic alloy has a saturation magnetic induction intensity of 7000-10000 Gs between 0.4 and 20 Oe when the thickness is 0.1-0.18 mm and the magnetic field frequency is 60 Hz; the soft magnetic alloy has a maximum magnetic permeability of 120-275 mH / m when the thickness is 0.1-0.18 mm and the magnetic field frequency is 60 Hz; the soft magnetic alloy has a coercive force of 0-4 A / m when the thickness is 0.1-0.18 mm and the magnetic field frequency is 60 Hz; the soft magnetic alloy has a room temperature resistivity of 40-100 μΩ·cm when the thickness is 0.1-0.18 mm and the magnetic field frequency is 60 Hz.
[0087] The present invention is further described below through specific examples.
[0088] Example 1
[0089] An aerosol-generating article for generating an inhalable aerosol when heated, comprising an aerosol-generating matrix segment, the matrix segment comprising an aerosol-generating matrix and a susceptor assembly, the susceptor assembly being configured to inductively heat the aerosol-forming matrix under the influence of an alternating magnetic field. The susceptor assembly is made of a soft magnetic alloy having a single-layer structure with uniform element distribution. The soft magnetic alloy has an average grain size of 50 to 70 μm and a grain size grade of 5.5 to 4.5. The composition of the soft magnetic alloy is shown in Table 1. The susceptor assembly is prepared as follows:
[0090] S1 weighed by mass alloy raw materials and coke, followed by smelting, remelting, hot forging blanking, hot rolling, cold rolling process to obtain cold-rolled material;
[0091] The smelting process is as follows:
[0092] According to the requirements of the total composition of the soft magnetic alloy product, iron, nickel, molybdenum and aluminum are weighed in a mass ratio of 2:9.5:0.6:0.025. At the same time, coke equivalent to half the total mass of iron, nickel, molybdenum and aluminum is added and placed in the charging area. The vacuum induction melting furnace is added from the charging area and vacuumized. Then the furnace is combined for smelting at a smelting temperature of 1500°C and a smelting time of 70 minutes. After melting, refining is continued. Manganese ore with a manganese content of 25% and a low-carbon ferrochrome with a chromium content of 55% are added during the refining process to achieve the purpose of alloying. The refining time is 1 hour and the refining temperature is 1600°C. After refining, it is poured at 1450°C, then demoulded and the furnace number is marked to obtain an ingot.
[0093] The remelting process is as follows:
[0094] The ingot was cut into 5x5x5mm pieces and polished to remove surface oil and rust. A graphite crucible lined with a 1wt% electrolytic nickel plate was placed inside a magnesia crucible. The ingot was then placed in the crucible, and 0.5wt% fused magnesia was added to the gaps between the ingots. The ingot was then placed in a vacuum induction melting furnace and evacuated. The furnace was then combined and smelted at 10kW power at a temperature of 1560°C for 60 minutes. 0.1wt% graphite carbon powder and 0.05wt% Si-Ca-Ba powder with a particle size of less than 1.0mm were added in three separate additions at a ratio of 2:1, with 8 minutes between additions. Finally, 0.05wt% molybdenum rod was added. After all raw materials were added, the refining time was 20 minutes, and the power was adjusted to 2kW. The temperature was lowered to 300°C, the circuit was shut off, and the vacuum was maintained. The sample was allowed to cool in the furnace to obtain a remelted ingot.
[0095] The hot forging process is as follows:
[0096] The pressure of the smelting furnace was relieved, and the crucible and the remelted ingot were taken out. The remelted ingot was placed in a chamber furnace, and the temperature in the furnace was raised to 1270°C in 60 minutes. After 10 minutes, it was hot forged into a 30mm flat billet under the action of a 2-ton steam hammer, and the surface was ground with a grinding wheel to obtain the billet.
[0097] The hot rolling process is as follows:
[0098] After the billet is heated to 1200℃, a four-roll reversible hot rolling machine is used. After three hot rolling cycles of 40min, 30min and 20min respectively, the thickness is reduced to 15mm, 10mm and 4mm respectively. The deformation temperature range of the hot rolling process is 1000-1200℃. The surface temperature of the hot-rolled plate is tested with an infrared thermometer. When the temperature is lower than 1000℃, the hot rolling is stopped to obtain the hot-rolled material.
[0099] The cold rolling process is as follows: the hot rolled material is cold rolled using a four-roll reversible cold rolling mill, the thickness of the cold rolled material is initially cold rolled to 1.2 mm, and the cold rolled material is further rolled using a four-roll reversible cold rolling mill to a thickness of 0.1 mm to obtain a cold rolled material;
[0100] S2. Anneal the cold-rolled material and the mixed powder in a vacuum hydrogen annealing furnace. The annealing process is as follows: anneal the cold-rolled material, prepare a 100-mesh mixed powder, and place it in a vacuum hydrogen annealing furnace along with the cold-rolled material. Raise the furnace temperature to 1030°C over 100 minutes, hold for 90 minutes, then reduce the temperature to 600°C at 200°C / hour, and then air-cool the material to 150°C at a cooling rate of 1800°C / hour before removing from the furnace. The mixed powder comprises the following components by weight: 45 parts Fe powder, 20 parts SiO2, 13 parts C powder, 16 parts Al2O3, and 6 parts MnO. The volume ratio of the mixed powder to the cold-rolled material is 0.05:100. The mixed powder and hydrogen form a powder airflow, which causes local oxidation on the alloy surface during the annealing process. Limited atomic exchange occurs between the elements in the mixed powder and the elements on the alloy surface. Since the atomic diameter is at the 0.1nm level, the effect of this local oxidation on the alloy composition can be ignored.
[0101] Example 2
[0102] An aerosol generating product for generating an inhalable aerosol when heated, the other contents of which are substantially the same as those of Example 1, except that during the preparation of the sensor assembly, the mass ratio of the smelting raw materials iron, nickel, molybdenum, and aluminum is controlled to be 2:10.5:0.65:0.025 during the smelting process.
[0103] Example 3
[0104] An aerosol generating product for generating an inhalable aerosol when heated, the other contents of which are substantially the same as those of Example 1, except that during the preparation of the sensor assembly, the mass ratio of the smelting raw materials iron, nickel, molybdenum, and aluminum is controlled to be 2:8.5:0.5:0.025 during the smelting process.
[0105] Example 4
[0106] An aerosol generating article for generating an inhalable aerosol when heated, the other contents of which are substantially the same as those of Example 1, except that the annealing conditions during the preparation of the susceptor assembly are such that the annealing temperature is 1300°C.
[0107] Example 5
[0108] An aerosol generating product for generating an inhalable aerosol when heated, the other contents of which are substantially the same as those of Example 1, except that during the preparation of the susceptor assembly, the secondary cooling condition is that the secondary cooling is carried out at 400°C / h and the product is cooled to 150°C before being taken out of the furnace.
[0109] Example 6
[0110] An aerosol generating article for generating an inhalable aerosol when heated, the other contents being substantially the same as those of Example 1, except for the annealing conditions during the preparation of the susceptor assembly and the holding time being 200 minutes.
[0111] Example 7
[0112] An aerosol generating article for generating an inhalable aerosol when heated, the other contents of which are substantially the same as those of Example 1, except that no mixing powder is added during the annealing process when preparing the susceptor assembly.
[0113] Comparative Example 1
[0114] An aerosol generating article for generating an inhalable aerosol when heated, the other contents of which are substantially the same as those of Example 1, except that the susceptor component is a commercially available alloy material, whose international brand is Hymu 80 alloy.
[0115] Comparative Example 2
[0116] An aerosol generating article for generating an inhalable aerosol when heated, the other contents of which are substantially the same as those of Example 1, except that the susceptor component is a commercially available alloy material, whose international designation is 1J77 alloy.
[0117] Comparative Example 3
[0118] An aerosol generating article for generating an inhalable aerosol when heated, the other contents of which are substantially the same as those of Example 1, except that the susceptor component is a commercially available alloy material, whose international designation is 1J79 alloy.
[0119] Comparative Example 4
[0120] An aerosol generating article for generating an inhalable aerosol when heated, the other contents of which are substantially the same as those of Example 1, except that the susceptor component is a commercially available alloy material, whose international brand is 1J85 alloy.
[0121] Comparative Example 5
[0122] An aerosol generating article for generating an inhalable aerosol when heated, the other contents of which are substantially the same as those of Example 1, except that the susceptor assembly is a multilayer susceptor composed of two layers of Hymu80 alloy and Fe-Cr alloy.
[0123] After element content analysis, the alloy composition was analyzed by inductively coupled plasma mass spectrometry combined with a sulfur and carbon analyzer. The composition ratios of the sensor assembly obtained according to the above method are shown in Table 1.
[0124] Table 1 Component ratios in soft magnetic alloys
[0125] Table 2 Physical properties of soft magnetic alloys
[0126] The surface of the soft magnetic alloy (sensor component) prepared in Example 1 was tested and observed using a metallographic microscope, and its schematic diagrams are shown in Figures 1 (100X) and 2 (200X). According to the GB~T~6394~2017 metal average grain size determination method, the alloy grain size grade in Example 1 was calculated to be 5.3 and the average grain diameter was 50.2 μm.
[0127] As shown in Figure 3, a field emission scanning electron microscope was used to test the surface morphology and an energy spectrometer was used to perform elemental analysis on local feature points. In Examples 1 to 6, a wide range of surface areas of the prepared soft magnetic alloy were scanned, and multiple types and multi-component defects on the surface of the material could be easily found. In Region 1, clustered defects were present, and the elemental composition of the four defects was basically similar. The elemental analysis is shown in Figure 4. The main inclusion elements include Fe, C, and O, and the oxide that can be formed is Fe3O4. In Region 2 of Figure 3, triangular defects were present. The elemental analysis is shown in Figure 5. The main inclusion elements include C, Al, O, and Si, and the oxides that can be formed are Al2O3 and SiO2. In Region 3 of Figure 3, circular defects were present. The elemental analysis is shown in Figure 6. The main inclusion elements include C, O, Mn, and S, forming inclusions of Mn compounds. Local inclusions on the alloy surface, on the one hand, cause a demagnetization field to be generated when the soft magnetic alloy is magnetized, and generate a magnetic domain structure inside the material, making magnetization difficult; secondly, the inclusion of oxides produces a pinning effect inside the alloy, increasing hysteresis loss and coercive force, which increases the external force work required for domain wall movement and makes it difficult to magnetize. The presence of oxides during the preparation process usually makes it difficult to magnetize the material, such as causing a decrease in maximum magnetic permeability and an increase in coercive force. In Example 7, the alloy surface was oxidized without adding mixed powders. By scanning a wide area of the surface, no multi-type and multi-component defects such as those in Example 1 were found. A typical graph of the test results is shown in Figure 7.
[0128] As shown in Figure 8, according to the A772 / A772M test standard, the magnetic properties of the soft magnetic alloy in Example 1 were tested. At a magnetic field frequency of 60Hz, it reached a saturation magnetic induction intensity of 7920Gs at around 0.7Oe, a maximum relative magnetic permeability of 154059 at 0.028Oe, and an absolute magnetic permeability of 194mH / m. As shown in Figure 9, the magnetic property test data in Comparative Example 1, at a magnetic field frequency of 60Hz, reached a saturation magnetic induction intensity of 7590Gs at around 0.5Oe, a maximum relative magnetic permeability of 192573 at 0.022Oe, and an absolute magnetic permeability of 243mH / m. There is a significant difference in magnetic permeability between Example 1 and Comparative Example 1. The maximum magnetic permeability in Example 1 decreased by about 50mH / m. However, the two are not much different in saturation magnetic induction intensity. The saturation magnetic induction intensity of Example 1 is slightly higher than that of Comparative Example 1 by about 330Gs.
[0129] Figure 10 shows a typical grayscale cross-sectional view of the soft magnetic materials prepared in Examples 1-7. As can be clearly seen, the test using epoxy resin embedded in the metal material reveals black areas on the upper and lower sides of the image, with the center portion of the black areas representing the alloy material. Combined with the grayscale cross-sectional view, grayscale view 10 shows that the image contrast is essentially uniform when viewed visually. The broadest color area within the main portion of the soft magnetic alloy accounts for at least 95% of the total area of the soft magnetic alloy, indicating that the material is a homogeneous layer.
[0130] As shown in Figures 11 and 12, the soft magnetic alloy component of Example 1 and a commercially available multilayer susceptor, whose material composition is a combination of Hymu80 and 430, were tested for Curie temperature. It was found that the Curie temperature of the multilayer susceptor was 402°C, and the magnetization intensity of the corresponding material was 61emu / g; in comparison, the Curie temperature of the single-layer iron core material was 385°C, and the magnetization intensity of the corresponding material was 10emu / g; this means that the demagnetization phenomenon of the single-layer iron core material near the Curie temperature is more significant, thereby alleviating the behavior of overheating the aerosol generating matrix.
[0131] As shown in Figure 15, the soft magnetic alloy components of Example 1 and Comparative Example 5 were loaded into an aerosol-generating product with a thickness of 0.1 mm, a width of 4 mm, and a length of 12 mm. The length of the aerosol-generating matrix segment was 12 mm, and the aerosol-generating matrix was a thick pulp tobacco sheet. The aerosol-generating product was then placed in a specific resonant wireless power transfer system (Magnetic Coupling Resonance Wireless Power Transfer, abbreviated as MCR-WPT). The surface heating temperature of the soft magnetic alloy component of the present application was tested, and it was found that its maximum temperature was 397°C. Compared with the maximum temperature of 384°C of the multilayer susceptor material in the same aerosol-generating product, the maximum temperature dropped by 13°C.
[0132] The above are only preferred specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or replacements that can be easily thought of by any technician familiar with this technical field within the technical scope disclosed by the present invention should be covered by the scope of protection of the present invention.
Claims
1. An aerosol generating article for generating an inhalable aerosol when heated, characterized in that The invention comprises an aerosol generating matrix section, wherein the matrix section comprises an aerosol generating matrix and a receptor component, wherein the receptor component induction heats the aerosol forming matrix under the influence of an alternating magnetic field, wherein the material of the receptor component is a soft magnetic alloy, and the soft magnetic alloy is a single-layer structure with uniform element distribution; the average grain size of the soft magnetic alloy is 50 to 70 μm, and the grain size grade is 5.5 to 4.
5.
2. An aerosol generating article for generating an inhalable aerosol when heated according to claim 1, characterized in that The components of the soft magnetic alloy include iron, molybdenum and nickel. The mass of the molybdenum accounts for 3.5% to 6% of the total mass of the soft magnetic alloy, and the mass of the nickel accounts for 77% to 81% of the total mass of the soft magnetic alloy.
3. An aerosol-generating article for generating an inhalable aerosol upon heating according to claim 1, characterized in that The soft magnetic alloy also includes chromium, and the mass of the chromium accounts for 0.2-0.5% of the total mass of the soft magnetic alloy.
4. An aerosol-generating article for generating an inhalable aerosol upon heating according to claim 1, characterized in that The soft magnetic alloy also includes manganese, and the mass of manganese accounts for 0.1% to 0.5% of the total mass of the soft magnetic alloy.
5. An aerosol-generating article for generating an inhalable aerosol upon heating according to claim 4, characterised in that The soft magnetic alloy also includes silicon and aluminum. The silicon content is 0.1% to 0.4%, and the aluminum content is 0.15% to 0.7%.
6. An aerosol-generating article for generating an inhalable aerosol upon heating according to claim 1, characterized in that The soft magnetic alloy comprises the following components in mass fractions: 77-81 parts of nickel, 3.5-6.0 parts of molybdenum, 0.2-0.5 parts of chromium, 0.1-0.5 parts of manganese, 0.1-0.4 parts of silicon, 0.15-0.7 parts of aluminum, and the balance 11-18 parts of iron.
7. An aerosol-generating article for generating an inhalable aerosol upon heating according to claim 1, characterized in that The sensor component has a thickness of 0.03-0.18 mm, a width of 1.5-4.5 mm, and a length of 9-18 mm.
8. An aerosol-generating article for generating an inhalable aerosol upon heating according to claim 1, characterized in that It also has a filter section and a cooling section, wherein the cooling section is located between the aerosol generating substrate section and the filter section; the aerosol generating substrate is made of tobacco material or non-tobacco material and is distributed in filaments, sheets or particles, and the receptor assembly is wrapped by the aerosol generating substrate.
9. An aerosol-generating article for generating an inhalable aerosol upon heating according to claim 1, characterized in that The preparation method of the sensor assembly comprises the following steps: S1. Weigh the alloy raw materials and coke by mass, and sequentially perform smelting, remelting, hot forging, hot rolling, and cold rolling processes to obtain a cold-rolled material; S2. placing the cold-rolled material and the mixed powder in a vacuum hydrogen annealing furnace for annealing treatment, the annealing temperature is 1000-1200°C, the holding time is 70-120min, the cooling rate is 150-220°C / h, after dropping to 580-630°C, air cooling or furnace cooling to 100-200°C.
10. An aerosol-generating article for generating an inhalable aerosol upon heating according to claim 9, characterised in that The mixed powder is a mixed powder of 100 to 300 meshes, including a mixture of Fe, MnO, SiO2, Al2O3, and C powders; the volume ratio of the mixed powder to the cold-rolled material is 0.05:100.